Hábitos posturales de riesgo para desarrolloar hiperlordosis, cifosis y escoliosis en los niños y niñas de la Escuela Manuel Monteros de Loja. - Mejía Baraja, Krupskaya Michelle (2017)
In the spinal column there are three physiological curvatures in the sagittal plane of the rachis, which are arranged opposite each other, which conditions a greater number of pathological possibilities and a greater difficulty in establishing the limits of normality. The pathological possibilities are: Increases of one or more curvatures, decrease of degree of curvature; and inversion of one or two curvatures. The most frequent one is the appearance of hipercifosis, and the hiperlordosis. Body posture refers to how the body is placed in space, that is, the position of the different skeletal segments and their location in space. The objectives of the present study are: To determine postural risk habits to develop hiperlordosis, cifosis and escoliosis in children aged 11 to 13 years in the Manuel Monteros de Loja school, as specific objectives: Identify postural habits that generate alterations (hiperlordosis, cifosis y escoliosis) in children aged 11 to 13 years. To know the frequency of alterations of the spine hiperlordosis cifosis y escoliosis in girls and boys aged 11 to 13. The research is descriptive and cross-sectional. In total there are 83 students between men and women. As conclusions about the alterations of spinal curvatures, we have: students evaluated from the Educational Institution Manuel Ignacio Monteros from 11 to 13 years on alterations of spinal curvatures, 15.62% have hiperlordosis, 8, 40% have escoliosis, and 4.80% have hiperlordosis. There is an incidence in the alterations of column by the weight of the backpack because those evaluated carry heavy backpack 53%, the same that carry with only one shoulder and with two. Postural habits have an impact on young people, as 39.8% have incorrect postures to lift light objects and 28.65% of students do not adopt a correct position in the chair. The existing school furniture in the educational institution does not fit the student's ergonomics in some cases the chairs are too large and in another case too small. Keywords: Habits, posture, kyphosis, lumbar hyperlordosis, scoliosis.